PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. CORT INDONESIA BAGIAN GUDANG PRODUKSI PAUL REED SMITH - Among Rizqi Prayogo; Ida Ayu Sri Brahmayanti (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the effect of transformational leadership style, communication and work discipline on employee performance at PT. Cort Indonesia Production Warehouse Section Paul Reed Smith. The place of this research is in the Bonded Zone of Ngoro Industri Persada, lot G number 5-6, Ngoro District, Mojokerto Regency. The time of research April – June 2022. This research used data sampling from 60 employees through questionnaires. The type of data used is quantitative. In this research, the t test showed that the Transformational Leadership Style variable has a partial effect on Y with the regression coefficient value of the Transformational Leadership Style (X1) of 0.027, the regression coefficient value of Communication (X2) of 0.013, and the regression coefficient value of Work Discipline (X3) of 0.001, thus each variable X has a positive and significant effect on variable Y. While the F test obtained f count > f table is 2.985 > 2.75 so it can be concluded that the independent variable Transformational Leadership Style (X1), Communication (X2), Work Discipline (X3) has a simultaneous and significant effect on the Employee Performance variable (Y). This research is expected to be a consideration for developing better employee performance than before. In addition, this research is expected to be considered a consideration for human resources development at PT. Cort Indonesia Production Warehouse Section of Paul Reed Smith in the future.